Review On The Analysis Of Qoe Applied In Serious Virtual Reality Games - Zegarra Rodriguez, Demostenes; SILVA AMARAL, Fernando Caio (INFOCOMP Journal of Computer Science, 2024)
Over time, electronic games have evolved from simple pixelated objects to complex expe- riences with a wide variety of narratives and user interactions, including various forms of immersion such as customized controls and games utilizing virtual reality (VR). VR allows users to interact with and perceive virtual objects in a more immersive way. Transitioning beyond mere entertainment, games have proven to be excellent educational tools for teaching various subjects and assisting in tasks like professional training across diverse fields, known as serious games. Through the use of virtual reality, individuals can visually learn through experiences such as virtual trips to aquariums, museums, and even the lunar surface. Healthcare professionals can practice surgical techniques using virtual patients, and production industry workers can operate machines without the need to halt real factory machinery for training purposes. While this technology is considered revolutionary by some, certain factors still hinder the widespread adoption of virtual reality by the general population. One primary concern reported by VR users is the occurrence of motion sickness and discomfort. Research is underway to enhance the user experience, but this remains an open challenge. Addressing this issue, user experience (QoE) research can be applied to assess and identify improvements. Thus, QoE enhancements not only contribute to user satisfaction but also maximize the educational benefits of these games. This study aims to evalu- ate key user complaints regarding the experience with specific games. Once these issues are identified, suggestions will be implemented, and a new round of user game experimentation, along with feedback collection, will be conducted. This refinement process is intended to be repeated iteratively, allowing the results to guide improvements in the Quality of Experience for serious games.